Mitochondria-associated gene expression perturbation predicts clinical outcomes and shows potential for targeted therapy in neuroblastoma - Chai, Chengwei; Chen, Yan; Luo, Yuanyuan; Zhang, Hong; Ye, Zhihua; He, Xiaobing; Zou, Yan; Xu, Yingyi; Li, Le; Tang, Jue; Wu, Qiang (Frontiers in Pediatrics, 2023)
Background: Mitochondria have long been considered a potential target in cancer therapy because malignant cells are known for their altered energy production. However, there is a lack of comprehensive research on the involvement of mitochondria-associated proteins (MAPs) in neuroblastoma (NB), and their potential as therapeutic targets is yet to be fully explored. Methods: MAP genes were defined based on the protein-coding genes with mitochondrial localization. The mRNA expression patterns and dynamics of MAP genes associated with NB were investigated by integrating publicly available transcriptional profiles at the cellular and tissue levels. Multivariate Cox regression analysis was conducted to reveal the association of MAP genes with the overall survival (OS) and clinical subgroups of NB patients. The single-cell RNA-seq dataset and gene dependency screening datasets were analyzed to reveal the therapeutic potential of targeting MAP genes. Results: We compiled a total of 1712 MAP genes. We found the global and cell type-specific mRNA expression changes of the MAP genes associated with NB status and survival. Our analyses revealed a group of MAP gene signatures independent of MYCN-amplification status associated with NB outcome. We provided computational evidence with selected MAP genes showing good performance in predicting long-term prognosis. By analyzing gene dependency of the MAP genes in NB cell lines and ex vivo human primary T cells, we demonstrated the therapeutic potential of targeting several MAP genes in NB tumors. Conclusions: Collectively, our study provides evidence for the MAP genes as extended candidates in NB tumor stratification and staging, prognostic prediction, and targeted drug development.